Functional MRI activation of the nucleus tractus solitarius after taste stimuli at ultra-high field: a proof-of-concept single-subject study - Canna, Antonietta; Cantone, Elena; Roefs, Anne; Franssen, Sieske; Prinster, Anna; Formisano, Elia; Di Salle, Francesco; Esposito, Fabrizio (Frontiers in Nutrition, 2023)
Using ultra-high field (7 Tesla) functional MRI, we conducted the first in-vivo functional neuroimaging study of the normal human brainstem specifically designed to examine neural signals in the Nucleus Tractus Solitarius (NTS) in response to gustatory stimuli. NTS represents the first relay station in the mammalian taste processing pathway, which starts from the taste buds in the oral cavity and passes through the thalamus, reaching the primary taste cortex in the brain. In our proof-of-concept study we acquired data from one adult volunteer participant using fMRI at a very high spatial resolution (1.2 mm isovoxel) and applied a univariate general linear model analysis approach. During fMRI acquisition, three repeated and shuffled injections of sweet, bitter, salty, sour and umami solutions were administered following an event-related design. We observed a statistically significant BOLD response in the anatomically predicted location of the NTS for all five basic tastes. The results of this study appear statistically robust, even though obtained in a single volunteer. The information derived from a similar strategy may gather a new research line applied to eating disorders for understanding details of central nervous system involvement and in designing and monitoring tailored therapeutic strategies.